2013
DOI: 10.1002/chem.201301679
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Hydrogenation of Ketones Catalyzed by Surface‐Active Ruthenium and Rhodium Complexes in Water

Abstract: An improved, high-yield, one-pot synthetic procedure for water-soluble ligands functionalized with trialkyl ammonium side groups H2 N(CH2 )2 NHSO2 -p-C6 H4 CH2 [NMe2 (Cn H2n+1 )](+) ([HL(n) ](+) ; n=8, 16) was developed. The corresponding new surface-active complexes [(p-cymene)RuCl(L(n) )] and [Cp*RhCl(L(n) )] (Cp*=η(5) -C5 Me5 ) were prepared and characterized. For n=16 micelles are formed in water at concentrations as low as 0.6 mM, as demonstrated by surface-tension measurements. The complexes were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 80 publications
2
21
0
Order By: Relevance
“…The capability of mixtures of RuL 8 and S to form mixed micelles was also assessed by measuring the corresponding diffusion coefficients. As reported previously, 28 the performance of RuL 16 (initial TOF 1400 h -1 ) and RuL 8 (TOF 350 h -1 ) in the hydrogenation of 1 differs significantly: the latter is less catalytically active and its reaction profile is sigmoidal with substantial induction period. At the Transfer hydrogenation of 1 catalyzed by the S/RuL n mixtures.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The capability of mixtures of RuL 8 and S to form mixed micelles was also assessed by measuring the corresponding diffusion coefficients. As reported previously, 28 the performance of RuL 16 (initial TOF 1400 h -1 ) and RuL 8 (TOF 350 h -1 ) in the hydrogenation of 1 differs significantly: the latter is less catalytically active and its reaction profile is sigmoidal with substantial induction period. At the Transfer hydrogenation of 1 catalyzed by the S/RuL n mixtures.…”
Section: Resultssupporting
confidence: 71%
“…28 We have shown that the most surface active RuL 16 complex is a better catalyst for hydrophobic ketones hydrogenation in aqueous media compared to the rhodium analogue RhL 16 . 28 We have shown that the most surface active RuL 16 complex is a better catalyst for hydrophobic ketones hydrogenation in aqueous media compared to the rhodium analogue RhL 16 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, use of rhodium complexes with P~N donor hemilabile ligands are less studied and needs to be addressed. Kalsin et al have recently reported the hydrogenation of ketone by a rhodium complex containing P~N hemilabile ligand in water and obtained good yield. Aydemir et al have reported same type of reaction with good yield.…”
Section: Resultsmentioning
confidence: 68%
“…In 2001 the first example of Ru(II)-catalyzed ATH of ketones with HCO 2 Na as a hydride source in aqueous media was reported [17]. Since this discovery, a number of water-soluble ligands and catalysts have been developed for ATH in aqueous media providing the reduction products in high conversion yields and enantioselectivities [18][19][20][21][22][23][24][25][26]. However, a major problem associated with these catalytic systems is that the low substrate/catalyst (S/C) ratio (normally S/C = 100) and large excess amounts of hydride donor (≥ 5 equiv.…”
Section: Introductionmentioning
confidence: 99%